Mutiny, mayhem, mythology : Bounty's enigmatic voyage - Frost, Alan, 1943- (Sydney University Press, 2018)
In 1789, as the Bounty was sailing through the western Pacific Ocean on its return voyage with a cargo of Tahitian plants, disgruntled crewmen seized control of the ship from their captain. The mutineers set their captain and the 18 men who remained loyal to him adrift in one of the ship's boats, with minimal food supplied and navigational aids, and only four cutlasses for weapons. Alan Frost looks past these common narrative structures to shed new light on what truly happened during the infamous expedition. Reviewing previous accounts and explanations of the voyage and subsequent mutiny, and.